Exploring mathematics teacher’s perceptions of students’ computational thinking and attitudes towards STEAM-AR: A need for module development - Masduki Masduki; Rita Pramujiyanti Khotimah; Sukirman Sukirman; Salsabila Kurniawati; Isnaini Nurul Hidayati (Journal of Research and Advances in Mathematics Education)
Computational thinking (CT) skills are vital for addressing future challenges. The integration of the Science, Technology, Engineering, Arts, and Mathematics (STEAM) can assist students to foster CT abilities. Furthermore, incorporating technology into education such augmented reality (AR) can improve the quality of the students’ learning experience. Consequently, it is essential to develop a STEAM-AR-based learning module to foster CT abilities. This study seeks to ascertain teachers' perceptions concerning students' CT abilities, attitudes towards STEAM learning principles, attitudes towards the technology integration in mathematics learning, and the need for a STEAM-AR-based mathematics module. An online survey was administered to 105 secondary mathematics teachers in the Sukoharjo District, Indonesia. The findings indicated that the teachers' perceptions were predominantly high. The high-level perceptions suggest that teachers view students as deficient in CT and STEAM-related learning activities. Furthermore, the findings demonstrate that the learning process will achieve higher quality by utilizing technology-based learning modules that integrate STEAM. In addition, there is no significant variation in teachers' perceptions based on gender and teaching experience across all perceptions. Finally, the results suggest that in order to improve students' CT abilities, teachers must integrate STEAM and technology into their classroom.